Teaching computer science in higher education: teachers concerns and students challenges for a better and successful learning - Fernando Miguel Rocha de Oliveira (2017)
This paper tends to present how eLearning strategies and policies used, in a Portuguese district (Aveiro), are enhancing learning and knowledge for heterogeneous audiences with constraints that are beyond the usual. Besides time to learn and physical distance, they face new challenges like, the need to get specialized in areas where economy is growing; where companies need to adapt to new markets; where the technology revolution is a priority. Experience achieved tells the professionals observed have shown great interest in eLearning actions and for a hybrid methodology. By a simple empirical evaluation, professionals agree that technologies are, in fact, very helpful for those who have several constraints to learn. They use the LMS in order to accomplish the learning assessments and skills but they also feel that there are a lot of improvements that can be done through ICT, especially to promote self- study. Rather than repositories, more intelligent and friendly content organization and actor’s participation could enable a more efficient learning.